Phakomatosis pigmentovascularis with sturge–Weber syndrome - Premanand Chandran; Snehal D Raut; Nithya Ramasamy; Ganesh V Raman (TNOA Journal of Ophthalmic Science and Research, 2020)
An 11-year-old boy presented with port-wine stain on the right side of the face and pigmentation of the sclera and iris in the left eye (LE). Fundus examination revealed inferior rim excavation of disc with orangish red tomato ketchup appearance of background retina suggestive of diffuse choroidal hemangioma in the right eye (RE) and normal retina in the LE. Ultrasonography showed increased thickness of retinochoroidal scleral complex, and swept-source optical coherence tomography showed choroidal thickening in the RE. He was diagnosed to have phakomatosis pigmentovascularis (PPV) with Sturge–Weber syndrome and glaucoma. PPV is a rare congenital disorder characterized by the presence of capillary malformation and pigmentary nevi. PPV can present with or without systemic involvement. Those without systemic involvement need to be followed up closely as they can manifest later in life.